Origin and Evolution of the W mineralization in the Intrusion-related Hydrothermal Deposits of the Cerro Áspero Mining District, Sierras Pampeanas, Argentina - González Chiozza, Sebastián (Anuário do Instituto de Geociências, 2021)
The Cerro Áspero Mining District (CAMD) is located at the Sierras Pampeanas of central Argentina and hosts significant intrusion-related wolframite mineralization. The ore deposits are associated to hydrothermal quartz veins and breccias, hosted by granitoids and metamorphic rocks at the northern contact zone of the Devonian post-orogenic Cerro Áspero Batholith (CAB). The physico-chemical conditions of the different mineralization styles are yet not totally understood, and aiming to deliver a metallogenetic model, the petrography and composition of the main ore and gangue minerals were investigated, and fluid inclusion and stable isotope studies were performed in quartz, muscovite, wolframite, apatite, pyrite, molybdenite, chalcopyrite, and galena. The integrated results revealed that the CAMD ore deposits were generated within the cooling period of the Cerro Áspero Batholith, throughout three late to post-magmatic hydrothermal mineralizing stages. Based on fluid inclusion studies and stable isotope processed data, it was found that the fluids of the first two stages were probably derived from a magmatic source, whereas the third stage solutions would have been originated from meteoric waters. The temperature of the system at the beginning of the hydrothermal phase, was estimated at 384°C; thereafter, the calculated values suggest a decreasing thermal path. Chemical analyses of wolframite showed that the CAMD ore deposit’s evolution was signed by initial formation of ferberite, and subsequently evolved with an increasing H/F ratio that conduced to hübnerite precipitation in the final stage.